IPM Strategies and Their Dilemmas Including an Introduction to www.eurowheat.org - Lise Nistrup Jørgensen; Mogens Støvring Hovmøller; Jens Grønbæk Hansen; Poul Lassen; Bill Clark; Rosemary Bayles; Bernd Rodemann; Kerstin Flath; Margot Jahn; Tomas Goral; J Jerzy Czembor; Philip Cheyron; et al. (Journal of Integrative Agriculture, 2014)
Information about disease management in winter wheat (Triticum aestiva) in eight European countries was collated and analysed by scientists and extension workers within the European Network for the Durable Exploitation of Crop Protection Strategies (ENDURE). This included information about specific disease thresholds, decision support systems, host varieties, disease prevalence and pathogen virulence. Major differences in disease prevalence and economic importance were observed. Septoria tritici blotch (Mycosphaerella graminicola) was recognized as the most yield reducing disease in countries with intensive wheat production, but also rust diseases (Puccinia striiformis and Puccinia triticina), powdery mildew (Blumeria graminis) and Fusarium head blight (Fusarium spp.) were seen as serious disease problems. Examples of current integrated pest management (IPM) strategies in different countries have been reported. Disease management and fungicide use patterns showed major differences, with an average input equivalent to 2.3 full dose rates (TFI) in the UK and a TFI of 0.6 in Denmark. These differences are most likely due to a combination of different cropping systems, climatic differences, disease prevalence, and socio-economic factors. The web based information platform www.eurowheat.org was used for dissemination of information and results including information on control thresholds, cultural practices which can influence disease attack, fungicide efficacy, fungicide resistance, and pathogen virulence, which are all elements supporting IPM for disease control in wheat. The platform is open to all users. The target groups of Euro Wheat information are researchers, advisors, breeders, and similar partners dealing with disease management in wheat.